Paul Samuelson's critique and equilibrium concepts in evolutionary game theory - Reinoud Joosten (Max Planck Institute of Economics, 2009)
We present two new notions of evolutionary stability, the truly evolutionarily stable state (TESS) and the generalized evolutionarily stable equilibrium (GESE). The GESE generalizes the evolutionarily stable equilibrium (ESE) of Joosten [1996]. An ESE attracts all nearby trajectories monotonically, i.e., the Euclidean distance decreasing steadily in time. For a GESE this property should holds for at least one metric. The TESS generalizes the evolutionarily stable strategy (ESS) of Maynard Smith & Price [1973]. A TESS attracts nearby trajectories too, but the behavior of the dynamics nearby must be similar to the behavior of the replicator dynamics near an ESS. Both notions are defned on the dynamics and immediately imply asymptotical stability for the dynamics at hand, i.e., the equilibrium attracts all trajectories sufficiently nearby. We consider this the relevant and conceptually right approach in defining evolutionary equilibria, rather than defining a static equilibrium notion and search for appropriate dynamics guaranteeing its dynamic stability. Moreover, the GESE and the TESS take similar positions as the ESE and ESE do in relation to other equilibrium and fixed point concepts in general.
Keywords: A12; C62; C72; C73; D83; 330; evolutionary stability; evolutionary game theory